Migration policy reforms in the context of economic and political crises: the case of Belgium. Issue 10 (8th August 2016) - Gsir, Sonia; Lafleur, Jean-Michel; Stanek, Mikolaj
ABSTRACT: A body of literature has examined the role of 'crises' on policy-making. Yet, we observe that endogenous or exogenous events called 'crisis-events' are often randomly chosen as sweeping explanations for reforms in migration and integration policy. Thus, we attempt to find answers for the question of how the latest financial and economic crisis affected policy-making in the area of migration and integration. We apply a combination of interest-based and ideas-based theories to the case of Belgium in order to question the role of crises in policy reforms in the field of migration and integration. Multiple political and economic crises have affected the country since 2007. Examining these crises and immigration politics we argue that electoral competition both between and within the Francophone and Flemish party systems continues to be the main driver of migration and integration policy reform. Yet, we also discover a cumulative effect of economic and political crises: while the intention of restricting immigration has remained largely unchanged over the years, the policy instruments employed to reach this objective have changed with the political and economic crises.